2023
DOI: 10.3389/fgene.2022.1033031
|View full text |Cite
|
Sign up to set email alerts
|

Uganda chicken genetic resources: I. phenotypic and production characteristics

Abstract: The extent of diversity in the indigenous chicken breeds of Uganda was assessed for their potential utilisation in breeding programmes. A total of 293 indigenous-chicken-keeping households in villages across 35 districts forming 12 sub-regions of the four regions were randomly sampled for 586 mature chickens of both sexes. While only 20.8% of households were headed by women, 40.6% of indigenous chicken keepers were women. The production objectives mainly focused on chickens as sources of income from sales and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This study detected and characterized virulence determinants of E. coli associated with the occurrence of diarrhoea in piglets in Ugandan settings. Overall, most of the respondents in the two study districts (75%) were males, which can be explained by the fact that most households in Uganda are headed by males, as also established by Yussif et al [ 28 ]. The present study also revealed that most (92.5%) of the respondents had attained formal education, a key factor in better management practices.…”
Section: Discussionmentioning
confidence: 57%
“…This study detected and characterized virulence determinants of E. coli associated with the occurrence of diarrhoea in piglets in Ugandan settings. Overall, most of the respondents in the two study districts (75%) were males, which can be explained by the fact that most households in Uganda are headed by males, as also established by Yussif et al [ 28 ]. The present study also revealed that most (92.5%) of the respondents had attained formal education, a key factor in better management practices.…”
Section: Discussionmentioning
confidence: 57%
“…This study, together with a preceding study ( Yussif et al, 2023 ), demonstrates the significance of a harmonized approach to AnGR characterization, where information on a production environment could be combined with phenotypic and molecular genetic data to guide decision-making. Indigenous chicken production under traditional husbandry conditions is characterized by the absence of pedigree data and records of origin.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, the chicken population in the western region showed the lowest genetic diversity estimates ( Table 1 ) in this study. An earlier phenotypic study in Uganda found the chicken population in the Western region to be lighter in weight with a higher rate of inbreeding compared to the other three regions ( Yussif et al, 2023 ). The non-significant negative F ST estimate obtained among the population in the eastern region is indicative of an absence of the population genetic structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations